A multispecies probiotic accelerates fear extinction and inhibits relapse in mice: Role of microglia. (1st August 2021) - Cui, Xiaoyu; Zhou, Songhua; Xia, Guang; Chen, Jie; Jiang, Lizhu; Huang, Jufang; Tong, Jianbin
Abstract: The relapse of fear memory remains a clinical challenge in treatment of fear-related disorders. Here we tested the effects and underlying mechanisms of probiotics treatment after fear conditioning on fear extinction. We found that fear conditioning induced synapse loss, microglial activation, and synaptic phagocytosis of activated microglial cells in hippocampal dentate gyrus of mice. And probiotics treatment (1 capsule/day/mice) after fear conditioning for 27 days inhibited these changes, promoted fear extinction, and inhibited the recovery of fear memory even 7 days after extinction. 16S rRNA gene sequencing demonstrated that probiotics supplement after fear conditioning partially normalized fear conditioning-induced dysbiosis of gut microbiota. In addition, we also found that repopulation of microglial cells in fear conditioning mice via PLX3397 treatment promoted long-term extinction of fear memory. Probiotics treatment after fear conditioning inhibited microglial activation and had similar therapeutic effects as the microglial cell repopulation induced by PLX3397 treatment. These data showed that (1) probiotics treatment after fear conditioning might promote long-term fear extinction which could be associated with the mitigation of synaptic pruning of activated microglial cells; (2) probiotics may be applicable as therapeutic strategy to inhibit microglial activation and treat fear-related disorders. Highlights: Probiotics treatment after fear exposure promotes fear extinction and limits relapse. Inhibiting microglial activation and its synaptic pruning is a possible mechanism. Microglia repopulation has similar treatment effects as probiotics.